2011
DOI: 10.1002/hep.24598
|View full text |Cite
|
Sign up to set email alerts
|

Protease profiling of liver fibrosis reveals the ADAM metallopeptidase with thrombospondin type 1 motif, 1 as a central activator of transforming growth factor beta

Abstract: During chronic liver disease, tissue remodeling leads to dramatic changes and accumulation of matrix components. Matrix metalloproteases and their inhibitors have been involved in the regulation of matrix degradation. However, the role of other proteases remains incompletely defined. We undertook a gene‐expression screen of human liver fibrosis samples using a dedicated gene array selected for relevance to protease activities, identifying the ADAMTS1 (A Disintegrin And Metalloproteinase [ADAM] with thrombospon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 43 publications
4
69
0
Order By: Relevance
“…At this point, we should recall the original cloning of mouse Adamts1 in a cachexia model 6 , a phenomena with a recognized inflammatory component. However, no further studies have focused exactly on this context, excluding a few references that revealed its genetic regulation by a variety of cytokines 6,49 .…”
Section: Discussionmentioning
confidence: 99%
“…At this point, we should recall the original cloning of mouse Adamts1 in a cachexia model 6 , a phenomena with a recognized inflammatory component. However, no further studies have focused exactly on this context, excluding a few references that revealed its genetic regulation by a variety of cytokines 6,49 .…”
Section: Discussionmentioning
confidence: 99%
“…While integrins, fibrinogen, and urokinase-type plasminogen activator are factors involved in TGF-β activation [46][47][48], TGF-β may be inactivated by the proteoglycan decorin [49]. In HSCs, ADAMTS1 induces TGF-β activation through an interaction of the latency-associated peptide with TGF-β, and its downregulation decreases the release of TGF-β [50].…”
Section: Tgf-β Superfamilymentioning
confidence: 99%
“…A number of proteases, including plasmin, matrix metalloproteinase (MMP)-2/9, and a disintegrin and metalloproteinase with TSP motifs 1 (ADAMTS1), have been identified as latent TGF-β activators in vitro (Lyons et al, 1988; Sato and Rifkin, 1989; Yu and Stamenkovic, 2000; Bourd-Boittin et al, 2011). Plasmin and MMP-2/9 belong to the serine protease and metalloproteinase families, respectively.…”
Section: Mechanisms Of Tgf-β Activationmentioning
confidence: 99%
“…A very recent study using a proteinase-related gene sample identified ADAMTS1 as an upregulated fibrosis-related protease in human liver fibrosis (Bourd-Boittin et al, 2011). ADAMTSs are characterized by an ancillary domain containing one or more TSP type 1 repeats (Apte, 2009).…”
Section: Tgf-β Activation Mechanism and Availability Of Latent Tgf-β mentioning
confidence: 99%